PERLAKUAN AKUNTANSI UNTUK ASET BERSEJARAH: PENGAKUAN, PENILAIAN DAN PENGUNGKAPANNYA DALAM LAPORAN KEUANGAN STUDI KASUS PADA MUSEUM ANJUK LADANG KABUPATEN NGANJUK - Dessy Wulandari; A.A. Gde Satia Utama (UNEJ e-Proceeding)
This study aims to determine the accounting treatment applied to the management of heritage assets in Anjuk Ladang Museum, both of recognition, valuation, presentation and disclosures in the financial statements. This research expected to provide clarity on the accounting standards heritage assets which should be implemented by the manager. This study used a qualitative method with case study approach. Data obtained by primary data from interviews and secondary data obtained from the supporting documents. The result of this study present the management of Museum recognizes Heritage Assets with "no value" because the life of the asset can not be easy determined. Accounting practices of heritage assets in the management still not appropriate with the standards set by the government, because it did not valuation and presentation heritage assets in notes of financial statement.